Co-transport and co-release of Eu(III) with bentonite colloids in saturated porous sand columns: Controlling factors and governing mechanisms. (1st April 2022) - Xu, Zhen; Pan, Duoqiang; Tang, Qingfeng; Wei, Xiaoyan; Liu, Chunli; Li, Xiaolong; Chen, Ximeng; Wu, Wangsuo
Abstract: Accurate prediction of the colloid-driven transport of radionuclides in porous media is critical for the long-term safety assessment of radioactive waste disposal repository. However, the co-transport and corelease process of radionuclides with colloids have not been well documented, the intrinsic mechanisms for colloids-driven retention/transport of radionuclides are still pending for further discussion. Thus the controlling factors and governing mechanisms of co-transport and co-release behavior of Eu(III) with bentonite colloids (BC) were discussed and quantified by combining laboratory-scale column experiments, colloid filtration theory and advection dispersion equation model. The results showed that the role of colloids in facilitating or retarding the Eu(III) transport in porous media varied with cations concentration, pH, and humic acid (HA). The transport of Eu(III) was facilitated by the dispersed colloids under the low ionic strength and high pH conditions, while was impeded by the aggregated colloids cluster. The enhancement of Eu(III) transport was not monotonically risen with the increase of colloids concentration, the most optimized colloids concentration in facilitating Eu(III) transport was approximately 150 mg L −1 . HA showed significant promotion on both Eu(III) and colloid transport because of not only its strong Eu(III) complexion ability but also the increased dispersion of HA-coated colloid particles. The HA and BC displayed a synergistic effect on Eu(III) transport, the co-transport occurred by forming the ternary BC-HA-Eu(III) hybrid. The transport patterns could be simulated well with a two-site model that used the advection dispersion equation by reflecting the blocking effect. The retarded Eu(III) on the stationary phase was released and remobilized by the introduction of colloids, or by a transient reduction in cation concentration. The findings are essential for predicting the geological fate and the migration risk of radionuclides in the repository environment. Graphical abstract: Image 1 Highlights: Colloid-driven transport of Eu(III) in porous media is related to colloid stability. A optimal colloids concentration exists in facilitating Eu(III) transport. HA and BC show synergistic effect on Eu(III) transport by forming ternary hybrid. The retarded colloids and Eu(III) is released as water chemistry condition varies.